Effect of Soybean Casein Digest Agar Lot on Number of Bacillus stearothermophilus Spores Recovered - Pflug, I. J. (1981)
In recent years it has become increasingly apparent that Bacillus stearothermophilus spores are affected by various environmental factors that influence the performance of the spores as biological indicators. One environmental factor is the recovery medium. The effect of different lots of commercial soybean casein digest agar on the number of colony-forming units per plate was examined in two series of experiments: (i) several lots of medium from two manufacturers were compared in single experiments, and (ii) paired media experiments with four lots of medium were carried out and yielded three-point survivor curves. The results demonstrate that commercial soybean casein digest agar is variable on a lot-to-lot basis. The variation was lowest when recovering unheated or minimally heated spores and increased greatly with the severity of heating.